Staging America Twenty-First-Century Dramatists - Bigsby, Christopher (Bloomsbury Academic, 2019)
A new generation of playwrights, whose careers began in this century, has emerged, and done so when American theatre and society was changing. Capturing the cultural shifts of 21st-century America, Staging America explores the lives and works of 8 award-winning playwrights - including Ayad Akhtar, Stephen Adly Guirgis, Young Jean Lee and Quiara Alllegría Hudes - whose backgrounds reflect the social, religious, sexual and national diversity of American society. Each chapter is devoted to a single playwright and provides an overview of their career, a description and critical evaluation of their work, as well as a sense of their reception.